Analysis of seasonal expression levels of wheat fructan exohydrolase (FEH) genes regulating fructan metabolism involved in wintering ability - Meguro-Maoka, Ayano (Journal of plant physiology, 2016)
Copyright © 2015 Elsevier GmbH. All rights reserved.